THE USE OF ACTIVETEACH AS A DIGITAL MEDIA TO IMPROVE LISTENING COMPREHENSION (A Classroom Action Research at Grade 8 of SMP Karya Bangsa Sintang) - Juniar, Rima (TELL - US JOURNAL, 2024)
Listening plays a crucial part in English language acquisition. This language skill is infrequently taught by the English teacher in the class. Classroom Action Research is used in this study in three cycles to collect the data. It was conducted in three meetings for each cycle. This study aimed to improve students’ listening comprehension in terms of accuracy of answers and understanding of main idea by using digital media in a form of application called ActiveTeach in teaching English to Grade 8 at SMP Karya Bangsa Sintang. The participants of this study were 22 students consisted of 10 females and 12 males of Grade 8 at SMP Karya Bangsa Sintang in academic year of 2022/2023. The findings showed that the use of ActiveTeach Wider World Level 3 to teach listening in terms of accuracy of answers and understanding of main idea improved the students’ listening comprehension. The listening activities given by using ActiveTeach improved students’ interest and curiosity to the learning materials since it offers audio and visual media to deliver the English materials. Furthermore, the listening test scores in each cycle were varied based on the students’ understanding of each material and the activities given during all the meetings.